AB0819 Axial Psoriatic Arthritis with and Without Radiological Involvement: Are There Any Differences?. (9th June 2015) - Almirall, M.; Salman, T.C.; Lisbona, M.P.; Iniesta, S.; Maymό, J.
Abstract : Background: CASPAR criteria for psoriatic arthritis (PsA) classification have as entry criteria inflammatory articular disease (joint, spine or entheseal). In 2009 Grappa group proposed diagnostic criteria for axial PsA, which include radiological involvement (non mandatory point). Objectives: The aim of this study was to evaluate differences between patients with axial Apso with and without radiological involvement in spine and/or sacroiliac joints. Methods: Descriptive, observational study, selecting consecutive patients from our department of Rheumatology with PsA fulfilling CASPAR criteria with axial involvement (Grappa criteria) with disease duration ≥5 years in 2013. Patients were divided in two groups, radiographic and non-radiographic axial PsA, according to the presence of suggestive radiology (unilateral or bilateral sacroiliitis grade 2 or more and/or syndesmophytes in spine). Differences in clinical, laboratory and radiological variables between patients with radiographic and non-radiographic axial PsA were evaluated. The variables assessed were: age, sex, disease duration, history/presence of peripheral involvement (arthritis, enthesitis or dactylitis), pattern of arthritis (oligoarticular or polyarticular), uveitis, family history of spondyloarthritis (including psoriatic arthritis) and/or psoriasis, therapy with synthetic disease-modifying antirheumatic drugs (sDMARD), with biologic disease-modifying antirheumatic drugs (bDMARD), with ≥2 bDMARD, HLAB27 positivity, history/presence of high CRP and/or ESR levels (CRP>0.6mg/dl and ESR>20mm/hour) and erosions in hands and/or feet in X-rays. The differences in baseline characteristics between both groups of patients were calculated by Student's t-test for quantitative variables and Chi-Square test for categorical variables. Results: Significantly more patients had oligoarticular pattern and family history of psoriasis in radiographic axial PsA group vs non-radiographic axial group (70.6% vs 25%, p=0.002 and 67.6% vs 37.5%, p=0.044). There were no statistically significant differences in other variables evaluated between two groups of axial PsA: radiographic and non-radiographic. Conclusions: The only statistically significant differences among patients with radiographic and non- radiographic axial PsA were the pattern of peripheral involvement and family history of psoriasis. Disclosure of Interest: None declared